2018
DOI: 10.1111/jpy.12751
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological diversity of Trebouxia microalgae in sphaerothallioid Circinaria spp. lichens1

Abstract: Three vagrant (Circinaria hispida, Circinaria gyrosa, and Circinaria sp. 'paramerae') and one crustose (semi-vagrant, Circinaria sp. 'oromediterranea') lichens growing in very continental areas in the Iberian Peninsula were selected to study the phycobiont diversity. Mycobiont identification was checked using nrITS DNA barcoding: Circinaria sp. 'oromediterranea' and Circinaria sp. 'paramerae' formed a new clade. Phycobiont diversity was analyzed in 50 thalli of Circinaria spp. using nrITS DNA and LSU rDNA, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Even though these results should be interpreted with caution due to the small number of specimens analysed, our study reveals that including metabarcoding analyses could be key to understanding the phycobiont relationship in these systems. Photobiont switching seems to be a ubiquitous phenomenon in lichens and appears to play a vital role in lichen adaptation to environmental conditions 46 , 47 , 60 64 . Association with a wide range of symbionts may help lichens survive under harsh environmental conditions 65 67 , such as those characterizing gypsum biocrusts in a low-dry ombroclimate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though these results should be interpreted with caution due to the small number of specimens analysed, our study reveals that including metabarcoding analyses could be key to understanding the phycobiont relationship in these systems. Photobiont switching seems to be a ubiquitous phenomenon in lichens and appears to play a vital role in lichen adaptation to environmental conditions 46 , 47 , 60 64 . Association with a wide range of symbionts may help lichens survive under harsh environmental conditions 65 67 , such as those characterizing gypsum biocrusts in a low-dry ombroclimate.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported that sequences showing double peaks, or polymorphic sequences, in electrophoretograms were removed from their analyses 41 , 44 , 53 ; perhaps those removed sequences constituted specimens showing algal coexistence in these lichen species, which were not taken into account. The ability of Sanger sequencing to address a wide variety of inquiries in lichen ecology and evolution is not in question, but it is important to point out that phycobiont coexistence could vary depending on the lichen species and could be the general rule in some lichen species 37 , 38 , 46 48 , 74 . We hypothesized that coexistence could be related to, or favoured by, specific thallus architectures, such as the crustose type, and this factor should be considered when studies about patterns of fungal-algal associations are carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illumina metabarcoding as well as the Sanger sequencing uncovered URa28 as a predominant phycobiont of Stereocaulon alpinum OTU2. In most cases, the phycobiont determined by the Sanger sequencing corresponds with a predominant phycobiont according to the high-throughput sequencing (Molins et al 2018; Paul et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the two mycobiont species-level lineages OTU2 and OTU35 differ in predominant phycobiont pool, they share the pool of other intrathalline algae, unlike two Circinaria spp. collected at the same location shared the predominant phycobiont, but showed a completely different pool of other intrathalline algae (Molins et al 2018). The Stereocaulon OTUs differ significantly in the frequency of intrathalline algae (Fig.…”
Section: Discussionmentioning
confidence: 99%